ANALISA PERBEDAAN KUALITAS HIDUP PEROKOK DENGAN BUKAN PEROKOK PADA MAHASISWA STUDI PENDIDIKAN DOKTER UNIVERSITAS ABULYATAMA - Aditya Candra; Rahmad Rahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Smooking habit is a common phenomenon in Indonesia that associated with the culture and regarded as a complex condition in society. This situation is based on the fact that the number of smoker continues to increase each year not only among male but also among female smokers. The high prevalence of smokking in Indonesia has significantly impacted on the premature death which causes the shortening of the human life span. This research, in particular, tries to investigate the significant difference in the quality of life score of male smoker and non smoker among the medical student of Abulyatama University. This study was an observational analytic research with a case-control design. There were 50 samples in this study consisted of 25 male smoker (case group) and 25 male non-smoker (control grup). The data collected by using the SF-36 questionnaire consisting of 36 questions. The independent sample test was used to find out the quality of life difference between the two groups. The data showed that about 17 smoker (41,5%) had a good quality of life and among all the non-smoker around 24 respondents (58,5%) proves to have a good quality of life. Further, the result revealed that there was a different status of quality of life between the smoker and non-smoker with the p value=0,01. Based on the study, it can be concluded that there is a significant difference in the quality of life of smokers and non smokers among the medical students of Abulyatama University.Keywords: Smoking, Independent sample test, SF-36 questionnaire